A Qualitative Study of Disability in Minority Veterans and Their Utilization of the VA Health System (International Journal of Scientific Research and Management (IJSRM), 2023)
Over time, as the United States army increased, white and minority citizens joined the military forces. This led to the establishment of the Veterans Bureau, and later the Veterans Administration, to care for the wounded soldiers. Although the nation had developed a system to provide services to veterans since the late 1700s, there has been a decline in utilization of y veteran service members in the modern day. The purpose of this phenomenological study is to investigate the causes behind the limited use of the mental health services provided by the VHA by minority veteran service members and to propose ways to improve these services. Additionally, another purpose was to examine any cases of discrimination against minority veteran service members based on interviews with participants and previous empirical literature. After conducting multiple interviews, the status of patient satisfaction, degree of reliance on VHA medical facilities, perception of efficiency of services, and patronage XIII were analyzed. In summary, previous empirical literature had indicated that minority veteran service members were more likely to face discrimination because of racial bias. However, today, that is not largely the case. Rather, most of the minority veteran service members interviewed did not face discrimination and they were content with the health services offered. While some of the interviewees did claim that they faced some acts of discrimination, the overwhelming majority did not. These findings suggest that most minority veteran service members do not face discrimination and that they are actively interested in seeking VH healthcare services. Nevertheless, understanding minority veteran service members may enable healthcare providers to provide them with customized healthcare sections.